2002
DOI: 10.1063/1.1504503
|View full text |Cite
|
Sign up to set email alerts
|

Unification of the Jaynes–Cummings model and Planck’s radiation law

Abstract: Articles you may be interested inIntegrability and superintegrability of the generalized n -level many-mode Jaynes-Cummings and Dicke models Decoherence and quantum-classical master equation dynamics A Lorentzian function based spectral filter for calculating the energy of excited bound states in quantum mechanics By combining iterative methods with Laplace transformation, we construct the solution of a dissipative Jaynes-Cummings model. The dissipative part of the model is based on the standard Markovian mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Even though this seems to be somewhat counterintuitive it could be shown that the interaction of a large reservoir in an arbitrary mixed initial state with a single qubit in a pure initial state can dynamically induce a nontrivial correlation [16,17]. More than that, the time-dependent appearance of entanglement has been evident from exact solutions of simple and also more complicated versions of the Jaynes-Cummings model in quantum optics [18][19][20][21]. By coupling a bipartite system (two qubits) to a heat bath of harmonic oscillators the non-Markovian dynamics starting from a separable initial state may also induce some entanglement on shorter or, exceptionally, even longer time scales [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this seems to be somewhat counterintuitive it could be shown that the interaction of a large reservoir in an arbitrary mixed initial state with a single qubit in a pure initial state can dynamically induce a nontrivial correlation [16,17]. More than that, the time-dependent appearance of entanglement has been evident from exact solutions of simple and also more complicated versions of the Jaynes-Cummings model in quantum optics [18][19][20][21]. By coupling a bipartite system (two qubits) to a heat bath of harmonic oscillators the non-Markovian dynamics starting from a separable initial state may also induce some entanglement on shorter or, exceptionally, even longer time scales [22].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1. Degree of entanglement E W (t) according to(20), in a first interval and for different initial states according to(19). The model parameters have been set to ε = = w = 2, u = 4, α = 0.01, ω c = 30, T = 0.…”
mentioning
confidence: 99%
“…The entanglement nature of the atom–photon state in the JCM was investigated in [ 5 ]. The dynamics of the atomic density operator of a dissipative JCM was examined in [ 6 ]. In that paper, the authors also provided the limit for obtaining the state with maximum value of von Neumann entropy.…”
Section: Introductionmentioning
confidence: 99%
“…See also [10]. Evolution of the atomic density matrix of a dissipative JC model was studied in [11]. They also proposed a limit for which the matrix converges to a state of maximum von Neumann entropy.…”
Section: Introductionmentioning
confidence: 99%